ANALISIS PROBLEMATIKA PELAKSANAAN PEMBELAJARAN TEMATIK PADA PEMBELAJARAN JARAK JAUH DI SDIT INSANTAMA LEUWILIANG BOGOR - Sulastri, Ana; lestari, hana; Hasanah, Tita (Prodi PGMI IAI Sahid, 2024)
This study aims to analyze the problems in the implementation of thematic learning in distance learning and provide alternative solutions to thematic learning during distance learning at SDIT Insantama Leuwiliang. To achieve this goal, this research was designed using a descriptive qualitative research type, with the research location at SDIT Insantama Leuwiliang. The research informants are school principals, teachers and students. Using audio recording research data types, field notes and documentation. Data collection techniques by way of observation, interviews and documentation. Testing the validity of the data using data source triangulation techniques. Data analysis uses the stages of data collection, data reduction, data presentation, and drawing conclusions. The results of this study indicate that the problems of implementing thematic learning in distance learning at SDIT Insantama Leuwiliang have several obstacles, including some children who are not equipped with mobile phones, are not accompanied by their parents, there is no signal at the student's home, children do not read all material and work on problems at random, and children feel dizzy and do not understand the learning material. The alternative solution to deal with this problem is by synergizing with parents and visiting students' homes.